2007
DOI: 10.1111/j.1540-5826.2007.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extended Time on the SAT® for Students with Learning Disabilities and/or Attention‐Deficit/Hyperactivity Disorder

Abstract: Accommodation policymaking and practice should be guided by empirical research and informed clinical judgment. Findings from our study can provide information to test users about the validity of inferences that can be made from scores obtained from accommodated test administrations for students with disabilities. The factor structure of the newly revised Scholastic Aptitude Reasoning Test (SAT , 2005) was examined across two groups of students (students without disabilities tested under standard time conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Ancestry and descendent searches were conducted using relevant studies and literature reviews (i.e., Chiu & Pearson, 1999;Fuchs & Fuchs, 2001;Gregg & Nelson, 2010;Johnstone, Altman, Thurlow, & Thompson, 2006;Koenig & Bachman, 2004;Sireci, 2008;Sireci, Li, & Scarpati, 2006;Thompson et al, 2002). Studies were excluded if the primary purpose was to (a) investigate classroom accommodations (e.g., MacArthur & Haynes, 1995), (b) investigate multiple accommodations where a specific one could not be determined (e.g., Elliott, Kratochwill, & McKevitt, 2001), or (c) investigate changes to the construct being measured (e.g., Lindstrom & Gregg, 2007). If other students with disabilities were included in the sample, the majority of students needed to be identified as LD.…”
Section: Literature Review Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancestry and descendent searches were conducted using relevant studies and literature reviews (i.e., Chiu & Pearson, 1999;Fuchs & Fuchs, 2001;Gregg & Nelson, 2010;Johnstone, Altman, Thurlow, & Thompson, 2006;Koenig & Bachman, 2004;Sireci, 2008;Sireci, Li, & Scarpati, 2006;Thompson et al, 2002). Studies were excluded if the primary purpose was to (a) investigate classroom accommodations (e.g., MacArthur & Haynes, 1995), (b) investigate multiple accommodations where a specific one could not be determined (e.g., Elliott, Kratochwill, & McKevitt, 2001), or (c) investigate changes to the construct being measured (e.g., Lindstrom & Gregg, 2007). If other students with disabilities were included in the sample, the majority of students needed to be identified as LD.…”
Section: Literature Review Proceduresmentioning
confidence: 99%
“…As such, studies were not included if numbers of students with LD were not reported or findings for these students were not disaggregated (e.g., Tindal et al, 1998). Studies were excluded if the primary purpose was to (a) investigate classroom accommodations (e.g., MacArthur & Haynes, 1995), (b) investigate multiple accommodations where a specific one could not be determined (e.g., Elliott, Kratochwill, & McKevitt, 2001), or (c) investigate changes to the construct being measured (e.g., Lindstrom & Gregg, 2007). Studies were reviewed for information about subjects (e.g., disability, grade), accommodation, measures (e.g., state test), methodology (e.g., well-controlled studies with comparisons between standard and accommodated administrations of parallel test forms, inclusion of students with and without disabilities), and findings (e.g., evidence of differential boost).…”
Section: Literature Review Proceduresmentioning
confidence: 99%
“…Unfortunately, this assumption has not received extensive empirical scrutiny. Lindstrom and Gregg (2007) evaluated performance on the Scholastic Aptitude Reading Test (SAT) for college students without disabilities tested under standard time conditions (n = 2, 476) relative to students with disabilities tested with extended time (n = 2, 476; 959 of whom had ADHD with or without LD). Approximately 80% of students with disabilities were provided time-and-a-half, while the remainder received double time.…”
Section: Educational Treatmentmentioning
confidence: 99%
“…More recently, Lindstrom and Gregg (2007) used confirmatory factor analysis (CFA) to examine the factor structures of the sections of the new SAT for nondisabled students who took the test at standard time and students with disabilities (learning disabilities, ADHD, or both) who took the test under extended time conditions. 3 To make the two groups equal in size, a random sample of nondisabled examinees was taken, leading to 2,476 students in each group.…”
Section: Construct Validitymentioning
confidence: 99%